Expression patterns of gamma-aminobutyric acid type A receptor subunit mRNAs in primary cultures of granule neurons and astrocytes from neonatal rat cerebella. - Bovolin, P (1992)
Using a competitive polymerase chain reaction assay, we have quantitated the absolute amounts of mRNA encoding 14 distinct subunits of the gamma-aminobutyric acid type A (GABAA) receptor in primary cultures of rat cerebellar granule neurons and cerebellar astrocytes. We found that the total amount of GABAA receptor subunit mRNA in astrocytes was 2 orders of magnitude lower than in neuronal cells. Furthermore, granule cell cultures expressed all 14 different GABAA subunit mRNAs, while the astroglial cultures contained detectable amounts of all the subunits expressed by granule cells except the alpha 6 and the gamma 2L subunits. Of the alpha subunit family members, the alpha 1, alpha 5, and alpha 6 mRNAs were prominent in granule cells, while the alpha 1 and alpha 2 mRNAs were abundant in astrocytes. Of the beta receptor subunit mRNAs, the beta 1 and beta 3 mRNAs were abundantly expressed in both cultures. The gamma 2S and gamma 2L mRNAs constituted the great majority of gamma subunit mRNAs in neurons, while the gamma 1 subunit mRNA was the most abundant gamma subunit mRNA in astrocytes. When various allosteric modulators of GABAA receptors were tested electrophysiologically, methyl 6,7-dimethoxy-4-ethyl-beta-carboline- 3-carboxylate (DMCM) was the only one to modulate chloride currents elicited by GABA in a significantly different manner in granule cells (negative modulation) compared with astrocytes (positive modulation). The latter effect was previously observed in transiently expressed recombinant GABAA receptors containing a gamma 1 instead of a gamma 2 subunit. Our quantitative mRNA results suggest that an important molecular determinant responsible for the DMCM-positive modulatory effect on astroglial native GABAA receptors is the presence of the gamma 1 subunit in the receptor assembly.